DESIGNING THE OLD VILLAGE PHOTOBOOK IN BATAM CITY - Hendi Sama; Hartono Hartono (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Old Village is a group of houses that functioned as a neighborhood where the original residents of the city of Batam lived before 1970 when Batam was built, which contains historical, local culture and religious values. The city of Batam has a history that is quite unique, when the city of Batam was growing, the original residents were like being eliminated and set in several different areas, the location of the residents of Batam was also mentioned as Old Village, for example Old Village Bengkong Laut. Bengkong Laut Old Village is very much bricked and has different and unique stories. Batam residents is also not familiar with the Old Village in Batam. The purpose of this research is to introduce Old Village to the public using a photobook. This photobook contains a collection of information about Old Village such as traditions, activities, food and the atmosphere of the place. In the process of designing a photobook, the author will use the Adobe Photoshop CC 2020 application to design photoshop. The author uses interview data collection techniques, location observations and also image documentation. The result of the implementation of this research is a printed photobook with a size of 20x20cm which contains photos for the introduction of the Old Village tradition. With this photobook, it is hoped that the people of Batam will know more about its history and add insight to the history of Old Village in Batam.